Evaluation of Science curriculum: A literature study - Amsal Alhayat; Zainal Arifin (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
The goals and roles of education are reflected in the implementation outlined through a series of curriculum plans. Science as a learning program also has a curriculum that serves as a reference for its performance in the classroom. Therefore, it is necessary to evaluate the science curriculum to determine the achievement of the established goals, considering various aspects within it. Hence, this research aims to describe the factors that need to be considered in evaluating the science curriculum as a learning program. The research method used is Systematic Literature Review (SLR), which involves the initial stage of identifying the keywords